Tawhid Uluhiyyah, Rububiyyah dan al-Asma’ wa al- Sifat Menurut Tafsiran Muhammad Rasyid Rida dalam Tafsir al-Manar - Abdullah, Mustaffa; Ibrahim, Ahmad Zaki (Jurnal Usuluddin, 2010)
The article discusses Muhammad Rashid Rida’s view pertaining to categories of tawhid i.e. al-Uluhiyyah, al-Rububiyyah and al-Asma’ wa al-Sifat. It also examines arguments and proofs advanced by him whether it is able to shed lights or not pertaining to Divine current issues in Malaysia.